Studi Netnografi Tentang Keputusan Konsumen Menggunakan Jasa Pesan Antar Makanan Online di Sidoarjo. - ranny buggy wahyu; nur diana; raditya koesdijarto putra; vinsa adi laksana; sigit hermawan (Program Studi Magister Manajemen FE Unsri, 2020)
ABSTRACT Research Objectives - This study aims to determine the effect of prices, products, promotions and distribution on consumer decisions using online food delivery services. Design / Methodology / Approach - The study was conducted by distributing questionnaires to 200 respondents who used an online food delivery service application, namely the Go-Food, GrabFood, McDelivery, KFC Online Delivery and Pizza Hut Delivery applications. This research uses ethnographic methods Findings - The results found that the decision to use online food delivery service is significantly influenced by e-marketing mix with e-place factor as the most dominant factor, while of all these factors it is known that e-product factors do not significantly influence user decisions online food delivery service in Sidoarjo. Originality / value - This research examines the influence of the marketing mix of prices, products, promotions and distribution with different digital concepts from previous studies that still use the traditional marketing mix concept. Keywords: e-Marketing mix, Consumer decision, Online food delivery.